13C Flux Analysis Reveals that Rebalancing Medium Amino Acid Composition can Reduce Ammonia Production while Preserving Central Carbon Metabolism of CHO Cell Cultures. Issue 10 (5th March 2018) - McAtee Pereira, Allison G.; Walther, Jason L.; Hollenbach, Myles; Young, Jamey D.
Abstract : 13 C metabolic flux analysis (MFA) provides a rigorous approach to quantify intracellular metabolism of industrial cell lines. In this study, 13 C MFA was used to characterize the metabolic response of Chinese hamster ovary (CHO) cells to a novel medium variant designed to reduce ammonia production. Ammonia inhibits growth and viability of CHO cell cultures, alters glycosylation of recombinant proteins, and enhances product degradation. Ammonia production was reduced by manipulating the amino acid composition of the culture medium; specifically, glutamine, glutamate, asparagine, aspartate, and serine levels were adjusted. Parallel 13 C flux analysis experiments determined that, while ammonia production decreased by roughly 40%, CHO cell metabolic phenotype, growth, viability, and monoclonal antibody (mAb) titer were not significantly altered by the changes in media composition. This study illustrates how 13 C flux analysis can be applied to assess the metabolic effects of media manipulations on mammalian cell cultures. The analysis revealed that adjusting the amino acid composition of CHO cell culture media can effectively reduce ammonia production while preserving fluxes throughout central carbon metabolism. Abstract : 13 C metabolic flux analysis is used to characterize the response of Chinese hamster ovary (CHO) cells to a novel medium variant designed to reduce ammonia production. Parallel 13 C labeling experiments determined that, while ammonia production decreased by roughly 40%, CHO cell metabolic phenotype, growth, viability, and monoclonal antibody (mAb) titer are not significantly altered by the changes in media composition. This study illustrates how 13 C flux analysis can be applied to assess the metabolic effects of media manipulations on mammalian cell cultures.